Microsoft Teams - Withee, Rosemarie (--For dummies., 2025)
"Looking for a fast and easy guide to Microsoft Teams, the collaboration software used by millions of people and companies around the world? In Microsoft Teams For Dummies, 3rd edition, you'll find the must-know tips, hidden tricks, and handy hacks you need to help you rock your workday and get things done lightning-fast. You'll learn how to incorporate Teams into your everyday workflow and use functionality like chatting, file sharing, team organization, videochat, and more. You'll even learn how to use Microsoft's brand-new AI companion Copilot to help you improve your processes and productivity"--